Patients' preferences in treatment for neovascular age-related macular degeneration in clinical routine. Issue 7 (25th April 2012) - Finger, Robert; Hoffmann, Andrea E; Fenwick, Eva K; Wolf, Armin; Kampik, Anselm; Kernt, Marcus; Neubauer, Aljoscha S; Hirneiss, Christoph
Abstract : Purpose: To assess the effect of ranibizumab treatment for neovascular age-related macular degeneration (nvAMD) on patients' preferences and vision-related quality of life (VRQoL) in a routine clinical setting. Methods: 55 treatment naïve patients were examined before and after the initial upload of three monthly injections of 0.5 mg ranibizumab. VRQoL was assessed using a Rasch-adjusted NEI-VFQ-25. Time trade-off (TTO), standard gamble, a visual analogue scale and the European Quality of Life Questionnaire (EQ-5D) were used to calculate utilities, and multiple logistic regression models were conducted to determine independent factors associated with utilities. Results: Mean±SD age was 75±7 years, and 40 patients (73%) were female. Mean±SD best-corrected visual acuity of the treated eye increased from 20/80 at baseline (logMAR 0.60±0.35) to 20/63 (logMAR 0.52±0.36; p=0.020) at follow-up after three injections. Utility score increases ranged from 2 utils (standard gamble anchored for death) up to 6.6 utils (EQ-5D German TTO, p=0.023) and visual functioning improved (Rasch adjusted composite NEI-VFQ score 50±21 to 54±21, p=0.042). Whether the worse or better eye was treated was not significantly associated with improvements in utility or VRQoL, whereas VA improvement in the treated eye was associated with an increase in utility (TTO, p=0.020). Conclusions: TTO performed best in this sample of elderly nvAMD patients undergoing anti-VEGF therapy. Better or worse eye treatment was not associated with a change in reported utilities or visual functioning in patients with newly diagnosed nvAMD. Directly elicited, vision-specific utilities gained with TTO seem to be sensitive to a change in vision status.